Genesis of Ultramafic Lamprophyres and Carbonatites at Aillik Bay, Labrador: A Consequence of Incipient Lithospheric Thinning beneath the North Atlantic Craton - Tappe, Sebastian; Foley, Stephen F.; Jenner, George A.; Heaman, Larry M.; Kjarsgaard, Bruce A.; Romer, Rolf L.; Stracke, Andreas; Joyce, Nancy; Hoefs, Jochen (Journal of Petrology, 2006)
ISSN:0022-3530 ISSN:1460-2415